2019
DOI: 10.1093/toxsci/kfz070
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Intracellular Calcium Stores Alleviates Neurological Morbidities in a DFP-Based Rat Model of Gulf War Illness

Abstract: Gulf War Illness (GWI) is a chronic multi-symptom disorder afflicting the veterans of the First Gulf War, and includes neurological symptoms characterized by depression and memory deficits. Chronic exposure to organophosphates (OPs) is considered a leading cause for GWI, yet its pathobiology is not fully understood. We recently observed chronic elevations in neuronal Ca 2+ levels ([Ca 2+ ] i ) in an OP-diisopropyl fluorophosphate (DFP)-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 59 publications
4
27
0
Order By: Relevance
“…We therefore used a combination of behavioral assays that measure certain aspects of signs of depression that are reported in humans. In agreement with our previous studies [32][33][34], DFP-exposed rats exhibited significantly higher immobility time in the FST, did not show higher preference towards sweetened water in the SPT, and exhibited lowered exploration in the open-arm of the EPM. Taken together, these behaviors suggest that repeated low-dose DFP exposure produces chronic neuropsychiatric signs in rodents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We therefore used a combination of behavioral assays that measure certain aspects of signs of depression that are reported in humans. In agreement with our previous studies [32][33][34], DFP-exposed rats exhibited significantly higher immobility time in the FST, did not show higher preference towards sweetened water in the SPT, and exhibited lowered exploration in the open-arm of the EPM. Taken together, these behaviors suggest that repeated low-dose DFP exposure produces chronic neuropsychiatric signs in rodents.…”
Section: Discussionsupporting
confidence: 93%
“…The activity of eEF2 kinase, also known as CamKIII, is modulated by calcium and calmodulin. We recently demonstrated that hippocampal neurons from GWI rats exhibited chronic calcium elevations [33,34]. It will be interesting to investigate the role of KET on GWI calcium homeostatic mechanisms and its subsequent effect on modulating the rapid behavioral response in this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, DFP is one of the most widely studied OP alkylphosphates in the laboratory (Prendergast et al, 1997;Prendergast et al, 1998;Pope et al, 2005;Grigoryan et al, 2008;Nallapaneni et al, 2008;Wright et al, 2010;Terry Jr et al, 2011;Terry Jr et al, 2012;Ferchmin et al, 2015;. Moreover, DFP is currently employed as an initiator of status epilepticus in seizure models (Deshpande et al, 2010;Todorovic et al, 2012;Pouliot et al, 2016) and a nerve agent surrogate in models of Gulf War Illness (O'Callaghan et al, 2015;Phillips et al, 2019). Nonetheless, there is a lack of information characterizing the cholinergic and noncholinergic mechanisms of OPs like DFP on hippocampal synaptic transmission.…”
mentioning
confidence: 99%
“…JPET # 263053 NMDAR in initiating Ca 2+ -induced Ca 2+ release mechanisms after OP exposure (Deshpande et al, 2010;Phillips et al, 2019). Interestingly, DFP has been shown to directly interact with the glutamate binding pocket of the NMDAR, irreversibly inhibiting the receptor (Johnson and Michaelis, 1992).…”
mentioning
confidence: 99%